Peluang Hukum Integrasi Sistem Resi Gudang Dengan Lembaga Keuangan Mikro Dalam Pembiayaan Petani Indonesia - Sudaryat, Sudaryat; Devina Monic Ritonga; Nadya Hanifah (Universitas Semarang, 2025)
The purpose of this study is to determine the legal constraints on integrating the warehouse receipt system with microfinance institutions and the benefits of this integration on farmer welfare. Indonesia has significant potential in agriculture and agribusiness. However, its utilization has not been optimal, as evidenced by the agricultural sector's fluctuating contribution to GDP between 2019 and 2023. One of the main obstacles is the lack of access to capital for farmers, which hinders productivity and business scale. The warehouse receipt system, which allows farmers to store their crops and use them as collateral for financing, has not met expectations, particularly for small-scale farmers. Formal financial institutions such as banks often have collateral requirements that are difficult for small-scale farmers to meet, and loans tend to be smaller due to the risk of declining commodity prices and quality during storage. This study presents the first comprehensive legal analysis examining the systematic integration of the warehouse receipt system and microfinance institutions within the regulatory context in Indonesia. Using normative juridical research methods and descriptive analysis, it is known that short-term bank funds are not suitable for agricultural credit needs that require longer terms. Microfinance institutions have not been able to utilize warehouse receipts as collateral due to regulatory limitations. Therefore, integration between the warehouse receipt system and microfinance institutions is crucial to improving access to financing for farmers, which is expected to increase productivity, farmer welfare, and the development of the agribusiness sector in Indonesia. Regulatory harmonization, in the form of horizontal synchronization between the Warehouse Receipt Law and the Microfinance Institutions Law, is recommended. Tujuan penelitian ini adalah untuk mengetahui kendala hukum integrasi sistem resi gudang dengan lembaga keuangan mikro dan manfaat integrasi resi gudang dan lembaga keuangan mikro pada kesejahteraan petani. Indonesia mempunyai potensi besar di bidang pertanian dan agribisnis. Namun, pemanfaatannya belum optimal, terlihat dari kontribusi sektor pertanian terhadap PDB yang fluktuatif antara 2019-2023. Salah satu kendala utama adalah kurangnya akses permodalan bagi petani, yang menghambat peningkatan produktivitas dan skala usaha. Sistem resi gudang, yang memungkinkan petani menyimpan hasil panen dan menggunakan resi sebagai agunan untuk pembiayaan, terutama bagi petani skala kecil belum sesuai dengan harapan. Lembaga keuangan formal seperti bank seringkali memiliki persyaratan agunan yang sulit dipenuhi oleh petani skala kecil, dan pinjaman yang diberikan cenderung lebih kecil karena terdapat risiko penurunan harga komoditas dan kualitas selama penyimpanan. Penelitian ini menghadirkan analisis hukum komprehensif pertama yang mengkaji integrasi sistematis antara sistem resi gudang dan lembaga keuangan mikro dalam konteks regulasi di Indonesia. Melalui metode penelitian yuridis normatif dengan analisis deskriptif diketahui bahwa dana perbankan yang bersifat jangka pendek tidak sesuai dengan kebutuhan kredit pertanian yang memerlukan jangka waktu yang lebih panjang. Lembaga Keuangan Mikro belum dapat memanfaatkan resi gudang sebagai agunan karena keterbatasan regulasi. Oleh karena itu, integrasi antara sistem resi gudang dan lembaga keuangan mikro sangat penting untuk meningkatkan akses pembiayaan bagi petani, yang diharapkan dapat meningkatkan produktivitas, kesejahteraan petani, dan pengembangan sektor agribisnis di Indonesia. Harmonisasi regulasi berupa sinkronisasi horizontal antara Undang-Undang Resi Gudang dan Undang-Undang Lembaga Keuangan Mikro menjadi rekomendasi.